1994
DOI: 10.1111/j.1748-1716.1994.tb09738.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and ventilatory responses to electrically induced cycling with complete epidural anaesthesia in humans

Abstract: Cardiovascular and ventilatory responses to electrically induced dynamic exercise were investigated in eight healthy young males with afferent neural influence from the legs blocked by epidural anaesthesia (25 ml 2% lidocaine) at L3-L4. This caused cutaneous sensory anaesthesia below T8-T9 and complete paralysis of the legs. Cycling was performed for 22.7 +/- 2.7 min (mean, SE) (fatigue) and oxygen uptake (VO2) increased to 1.90 +/- 0.13 1 min-1. Compared with voluntary exercise at the same VO2, increases in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…E ciency of electrically induced movements relative to that of voluntary exercise has been found to be 1 : 4, by use of epidural anaesthesia and electrically induced cycling in able-bodied subjects. 11 In line with these facts e ciency of electrically induced exercise in SCI individuals (calculated to approximately 4%) is very low compared to that of voluntary exercise. 29 It follows that unloaded exercise with an ergometer power output of zero on the equipment we used should not necessarily be considered useless from a training perspective.…”
Section: Total Work Outputmentioning
confidence: 76%
See 1 more Smart Citation
“…E ciency of electrically induced movements relative to that of voluntary exercise has been found to be 1 : 4, by use of epidural anaesthesia and electrically induced cycling in able-bodied subjects. 11 In line with these facts e ciency of electrically induced exercise in SCI individuals (calculated to approximately 4%) is very low compared to that of voluntary exercise. 29 It follows that unloaded exercise with an ergometer power output of zero on the equipment we used should not necessarily be considered useless from a training perspective.…”
Section: Total Work Outputmentioning
confidence: 76%
“…However, it has been shown that FES gives rise to higher increases in lactate than voluntary exercise in able-bodied individuals. 11 In healthy subjects the cardiac pump capacity limits VO 2 -max. If a small muscle mass is used, the maximal cardiac pump activity cannot be reached.…”
Section: Changes In Vo 2 -Maxmentioning
confidence: 99%
“…The average workrate for this oxygen cost was found to be approximately 120 W during volitional cycling, but less than 40 W for FES-cycling. From data presented in the paper, [15], we estimate the net efficiencies for FES-cycling and for volitional cycling in this group to be 7% and 22%, respectively. This establishes that even in subjects where the underlying muscle condition is normal, FES-induced cycling is less efficient by a factor of approximately 3 than cycling achieved by volitional muscle control.…”
Section: Introductionmentioning
confidence: 99%
“…Kjaer et al [15] investigated the performance of eight healthy young males in both volitional and FES-induced cycling. The group performed volitional cycling at a workrate which elicited an average oxygen uptake of 1.9 l · min −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Both reduced exercise tolerance on a treadmill walking test 6 and reduced cardiorespiratory fitness (maximal oxygen consumption [VO 2 max]) on a cycle ergometer 7 compared with able-bodied control subjects have been shown in adolescent renal transplant recipients. Reductions in VO 2 max compared with agematched healthy individuals 8 and limitations in daily functioning were noted in adult LT recipients. [9][10][11] To the best of our knowledge, no research has been conducted on the assessment of fitness levels in pediatric LT recipients.…”
mentioning
confidence: 96%